Analysis of Eating Habits According to Socio-Demographic Characteristics of College Students - Musingo, Mitwe N.; Wang, Lihong (Pakistan Journal of Nutrition, 2009)
The purpose of this study was to analyze eating habits according to socio-demographic characteristics of college students. The study used a convenience sample of 212 students attending Florida A and M University (FAMU), a Historically Black College and University (HBCU) institution located in Tallahassee, Florida. The three nominal independent variables used in the survey to assess the socio-demographic characteristics of the students were gender, residential status and academic classification. Nearly 72% of the students (n = 152) were females and 28% were males (n = 60); 72% lived off campus in their own houses or apartments (n = 153) and 28 % lived on campus in FAMU dormitories and housing units (n = 59). The academic classification of these 212 students included 65 freshmen (31%), 60 sophomores (28%), 40 juniors (19%), 32 seniors (15%) and 15 graduates (7%). More than half of the students (58%) were between 18 and 20 years old; 36% were between 21 and 24 years old and only 6% were 25 years and older.